(untitled) - Lucas, Robert W. (San Francisco, CA, 2009)
This important book offers trainers and effective and efficient approach for designing training workshops and sessions that incorporate concepts from research on how the human brain best obtains, retains and recalls information. Includes information on selecting a topic specifically to address audience needs and provides a step-by-step guidance for creating an effective outline, designing and developing support materials, selecting appropriate location (to include equipment and furnishings), and provide tips for presenting the content to learners in a creative and professional manner. This important book offers trainers and effective and efficient approach for designing training workshops and sessions that incorporate concepts from research on how the human brain best obtains, retains and recalls information. Includes information on selecting a topic specifically to address audience needs and provides a step-by-step guidance for creating an effective outline, designing and developing support materials, selecting appropriate location (to include equipment and furnishings), and provide tips for presenting the content to learners in a creative and professional manner.
Keywords: Workshops (Adult education),Employees,Hội thảo (giáo dục dành cho người lớn),Nhân viên; Training of.,Đào tạo